2023
DOI: 10.1136/ard-2022-223626
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine metabolism inhibits arthritis and inflammatory bone loss

Shan Cao,
Yixuan Li,
Rui Song
et al.

Abstract: ObjectivesTo investigate the effect of the L-arginine metabolism on arthritis and inflammation-mediated bone loss.MethodsL-arginine was applied to three arthritis models (collagen-induced arthritis, serum-induced arthritis and human TNF transgenic mice). Inflammation was assessed clinically and histologically, while bone changes were quantified by μCT and histomorphometry. In vitro, effects of L-arginine on osteoclast differentiation were analysed by RNA-seq and mass spectrometry (MS). Seahorse, Single Cell EN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Vitamin B6, which has been reported to mitigate negative effects induced by reactive oxygen species via inhibition of xanthine oxidase activity, was found to exert a protective effect on cartilage by regulating oxidative stress, a pivotal factor implicated in various pathologies including osteoarthritis [ 25 ]. l -arginine was demonstrated that l -arginine alleviated arthritis pathology, inflammatory osteoclastogenesis and inflammation-induced bone loss by modulating amino acid metabolism in osteoclasts [ 26 ]. Similarly, l -proline plays a vital role in collagen synthesis, which is essential for tendon and joint health.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B6, which has been reported to mitigate negative effects induced by reactive oxygen species via inhibition of xanthine oxidase activity, was found to exert a protective effect on cartilage by regulating oxidative stress, a pivotal factor implicated in various pathologies including osteoarthritis [ 25 ]. l -arginine was demonstrated that l -arginine alleviated arthritis pathology, inflammatory osteoclastogenesis and inflammation-induced bone loss by modulating amino acid metabolism in osteoclasts [ 26 ]. Similarly, l -proline plays a vital role in collagen synthesis, which is essential for tendon and joint health.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Recent studies identified positive roles for arginine in preventing inflammation and osteoclastogenesis in arthritis and measured higher serum levels of arginine and ornithine in patients with RA. 27 28 Unfortunately, one limitation of using NMR metabolomics is that the resonances used to identify arginine in 1 H NMR spectra overlap with those from lysine. 29 Therefore, we could not specifically quantify the serum concentration of arginine.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is closely related to bone metabolism. Chronic inflammation and inflammatory environment are the common causes of bone loss ( 82 ). Innate immune responses are involved in the development and maintenance of inflammation.…”
Section: Roles Of Inflammatory Factors In Osteoporosismentioning
confidence: 99%